2021
DOI: 10.1038/s41592-021-01156-w
|View full text |Cite
|
Sign up to set email alerts
|

Best practices and tools for reporting reproducible fluorescence microscopy methods

Abstract: Although fluorescence microscopy is ubiquitous in biomedical research, microscopy methods reporting is inconsistent and perhaps undervalued. We emphasize the importance of appropriate microscopy methods reporting and seek to educate researchers about how microscopy metadata impact data interpretation. We provide comprehensive guidelines and resources to enable accurate reporting for the most common fluorescence light microscopy modalities. We aim to improve microscopy reporting, thus improving the quality, rig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 64 publications
0
65
0
Order By: Relevance
“…Reproducibility of fluorescence microscopy methods was previously identified as a major issue [41]. Quantitative fluorescence microscopy is inherently difficult to reproduce, due to the large number of factors involved.…”
Section: Discussionmentioning
confidence: 99%
“…Reproducibility of fluorescence microscopy methods was previously identified as a major issue [41]. Quantitative fluorescence microscopy is inherently difficult to reproduce, due to the large number of factors involved.…”
Section: Discussionmentioning
confidence: 99%
“…To coat the coverslip, we dipped the coverslip in PolyLys solution for 2 min, washed it with water, and dried it. The slides were visualized using a Zeiss 780 confocal microscope equipped with a 63×/1.4 Plan-Apochromat oil immersion objective ( 47 ). Images were processed by merging the two-color channels in FIJI, a distribution of imageJ2, without changing the pixel intensity ( 48 ).…”
Section: Methodsmentioning
confidence: 99%
“…A recent exploration about the quality of published Method sections in scientific articles containing images obtained with advanced microscopes, found that the quality of reporting was poor, with some articles containing no information about how images were obtained, and many articles lacking important basic details (13). Nonetheless, there is ample evidence that the publication of full details about how each image was obtained is vital for rigor, reproducibility and maximal scientific and sharing value (14)(15)(16)(88)(89)(90). In this context, the 4DN-BINA-OME Microscopy Metadata specifications presented are intended to provide a major contribution towards the development of community-driven criteria for which information should be included in the Methods sections of scientific publications.…”
Section: Model Implementation: Materials and Methods Recommendationsmentioning
confidence: 99%